Influence of Islamic Architecture on Residential Structures in the Hausa Community - Aisha Abdulkarim Aliyu; Alice Sabrina Ismail (Journal of Islamic Thought and Civilization, 2023)
The architectural traditions of Islamic cultures have been influenced by Islamic teachings historically. These teachings include values, such as discretion, modesty, and hospitality. These values work as guiding principles and impact the construction of Muslim houses, arrangement of spaces, and interaction of people with one another. However, the current political and social shifts, together with the ideas departing from Islamic cultural values are rather upsetting for Muslims. Resultantly, some of the architectural styles have emerged that go against the ideals and principles, upheld by Islamic beliefs. The current study, in connection with the influence of Islamic cultural values, attempted to examine the shape, traits, and components of housing, thoroughly. Moreover, it also focused on the interactions between these elements in different Islamic towns with different environmental conditions as well. Two case studies were conducted in the Kano metropolitan region by employing a qualitative methodology. This methodology comprised document analysis and direct observation presented within the context of interpretivist research paradigm. The findings showed that religious beliefs form the basis of regional design, with Islamic civilizations' architectural works deriving their inspiration directly from the Islamic principles. The academics underlined the significance to understand Islamic beliefs and values while taking into account the evolving conditions surrounding the contemporary designs in light of the research findings. This knowledge is essential to properly articulate the local Islamic identity in a way that responds to the demands of contemporary society.